Percutaneous Transluminal Renal Angioplasty Remarkably Improved Severe Hypertension and Renal Function in a Patient with Renal Artery Stenosis and Postrenal Kidney Failure. (May 2013) - Ishida, Ryo; Komaki, Kazumi; Nakayama, Mayuka; Sonomura, Kazuhiro; Nakanouchi, Tsuneyuki; Naya, Yoshio; Mori, Yasukiyo; Kusaba, Tetsuro
<x xml:space="preserve">Abstract</x> A 69-year-old man was admitted to our hospital with severe hypertension and rapidly worsening renal function. He presented with a 10-year history of chronic renal failure caused by bilateral ureteral obstruction due to retroperitoneal fibrosis. Magnetic resonance angiography and Doppler ultrasonography suggested severe right renal artery stenosis (RAS). Renal angiography revealed 99% stenosis at the ostium of the right renal artery. We performed percutaneous transluminal renal angioplasty (PTRA) with the support of intravascular ultrasound to decrease the amount of contrast agent needed. In addition, to prevent distal atheroembolism, a distal protection device was used. The procedure was completed without any adverse effects. After PTRA, renal function and blood pressure improved remarkably and remained stable for one year. PTRA for RAS remains controversial, especially in patients with renal insufficiency. Use of new devices should be considered to decrease catheterization-related adverse effects.